Home away home: Adjustment experience of Bangladeshi immigrants in the Netherlands - Farid, KS (Journal of the Bangladesh Agricultural University, 2016)
Adjustment into a new culture is of crucial importance for the immigrants to lead a meaningful life in that culture. The present study investigates the adjustment experiences of Bangladeshi immigrants in the Netherlands by exploring and describing the nature of psychological, socio-cultural, and economic adjustment. Participants were 14 Bangladeshi immigrants aged between 29 and 62 years who were selected through snowball sampling technique, were directly or indirectly related with restaurant business and had been residing in the Netherlands for at least five years. A qualitative approach to data collection and analysis was employed in order to get insights from the study participants. For collecting data, in-depth interviews were conducted among the study participants. Data analysis was done with the use of MAXQDA qualitative data analysis software. Examination of the interview transcripts revealed that the immigrants are psychologically happy with their well-being, as almost all of their expectations have been fulfilled despite some problems of cultural differences. Bangladeshi immigrants maintain socio-cultural relationship with the people sufficient to lead normal daily lives as they do hardly face any problem. However, there interaction with Dutch is limited. Though they are not completely happy with their busy lives in the Netherlands, they feel better here compared to Bangladesh. They are economically adjusted because of the fulfilment of their economic expectations. Several practical implications were elicited from the research including a need for programmes that promote immigrants integration with the mainstream of the Dutch society by encouraging the broadening of social relationship. J. Bangladesh Agril. Univ. 12(2): 345-350, December 2014